Антология выдающихся достижений в науке и технике. Часть 46: Термоядерная энергетика. Термоядерные реакторы и электростанции: ретроспектива исследований управляемого термоядерного синтеза, их современное состояние и будущее - Баранов, М.И. (Електротехніка і електромеханіка, 2018)
Приведен научно-технический обзор о ретроспективе исследований в ведущих странах мира управляемого термоядерного синтеза (УТС) легких ядер, современном состоянии разработок и возможных перспективах мирового развития наукоемкой техники в области термоядерной энергетики. Приведены ядерно-физические основы процесса протекания УТС в смеси легких ядер. Представлены данные о результатах начального и современного этапов исследований
в области УТС. Описаны основные конструкции и технические характеристики термоядерных реакторов (ТЯР),
использующих магнитное и инерционное удержание горячей плазмы. Проанализирован мировой прогресс в области
разработки, создания и исследования экспериментальных ТЯР, базирующихся на системах удержания горячей плазмы в тороидальных магнитных «ловушках» (установки-токамаки и стеллараторы) и инерционных системах лазерно-импульсной технологии микровзрывов мишеней-капсул термоядерного топлива. Приведены данные об основных
видах термоядерного топлива, которое может применяться в рабочих циклах ТЯР, и безопасности ТЯР. Указаны
основные проблемы в области УТС для экспериментальных ТЯР и создания в будущем термоядерных электрических
станций (ТЯЭС). Отмечена важная роль ТЯЭС и термоядерной энергетики в обеспечении человечества в долгосрочной перспективе электроэнергией. Наведено науково-технічний огляд про ретроспективу досліджень в провідних країнах світу керованого термоядерного синтезу (КТС) легких ядер, сучасний стан розробок і можливі перспективи світового розвитку наукоємної техніки в
області термоядерної енергетики. Приведені ядерно-фізичні основи процесу протікання КТС в суміші легких ядер.
Представлені дані про результати початкового і сучасного етапів досліджень в області КТС. Описані основні конструкції і технічні характеристики термоядерних реакторів (ТЯР), що використовують магнітне і інерційне утримання гарячої плазми. Проаналізований світовий прогрес в області розробки, створення і дослідження експериментальних ТЯР, що базуються на системах утримання гарячої плазми в тороїдальних магнітних «пастках» (установкитокамаки і стеларатори) і інерційних системах лазерно-імпульсної технології мікровибухів мішеней-капсул термоядерного палива. Приведені дані про основні види термоядерного палива, яке може застосовуватися в робочих циклах
ТЯР, і безпеку ТЯР. Вказані основні проблеми в області КТС для експериментальних ТЯР і створення в майбутньому
термоядерних електричних станцій (ТЯЕС). Відмічена важлива роль ТЯЕС і термоядерної енергетики в забезпеченні
людства в довгостроковій перспективі електроенергією. Purpose. Preparation of brief scientific and technical review
about the retrospective view of investigations, state-of-the art,
problems and possible prospects of development in the world of
thermonuclear power engineering. Methodology. Known scientific methods of collection, analysis and analytical treatment of the
opened scientific and technical information of world level in area
of the controlled thermonuclear synthesis (CTS) and thermonuclear power engineering, resulted in scientific monographs, journals and internet reports. Results. A brief analytical scientific and
technical review is resulted about the retrospective view of researches, modern state, basic achievements, existent problems
and possible prospects of development of thermonuclear power
engineering in the leading countries of the world. Nuclear physical bases of process of flowing of CTS are resulted in mixture of
light nuclei. Information is presented about the results of the initial and modern stages of world researches in area of CTS. Basic
constructions and technical descriptions of thermonuclear reactors (TNR), utilizing the magnetic and inertia withholding of hot
plasma are described. World progress is analyzed in area of development, creation and research of experimental TNR, being
based on the systems of withholding of hot plasma in toroidal
magnetic «traps» (options: tokamaks and stellarators) and inertia
systems of laser-impulse technology of microscopic explosions of
targets-capsules of thermonuclear fuel. Information is resulted
about the basic types of thermonuclear fuel, which can be used in
the duty cycles of TNR, and safety of TNR. The basic systems and
devices of the largest in the world of experimental TNR-tokamak
of ITER type (with a reference cost of EUR 15 billion and term of
putting into an experimental operation in 2025), erected now
within the framework of international project in France are described. Basic problems are indicated in area of CTS in experimental TNR and creations in the future of the thermonuclear
power plants (TNPP). The important role of TNPP and thermonuclear power engineering is marked on the whole in providing of
humanity in a long-term prospect electric energy. Originality.
Certain systematization of the scientific and technical materials
touching the problem of CTS of light nuclei and practical application in the peaceful aims of thermonuclear energy known from the
sources opened in outer informative space is executed. It is shown
on the basis of approach of the systems, that, in spite of row of
existent technical problems in area of creation of industrial TNR
and practical commercial capture thermonuclear energy, thermonuclear power engineering has an important value for providing
in remote future electric energy of all of humanity. Practical
value. Scientific popularization and deepening for the students of
technical universities, engineering, technical and scientific workers, working in the power sector of economy, scientific and technical knowledge in area of CTS and thermonuclear power engineering, extending their scientific range of interests and further
development of scientific and technical progress in society